Enhancing Global Competency and Academic Excellence: A Strategic Analysis of FITK UIN Malang's Path to Becoming a World-Class University - Marno; Choridah, Rifka Arifatul; Zhafirah, Azka Ilma; Assidiqi, Mokhammad Ilham (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2023)
This research delineates the strategic endeavors of the Faculty of Tarbiyah and Teacher Training (FITK) at UIN Maulana Malik Ibrahim Malang to bolster student achievements, aspiring to evolve into a world-class university. Embracing a qualitative methodology, the study employs critical analytical descriptive methods to probe student coaching development strategies, resources, and outcomes at FITK. Data sources span strategic plans, educational guidelines, stakeholder interviews, and Focus Group Discussions (FGDs). From 2020 to 2022, it marked a pivotal era, witnessing a surge in student accomplishments at regional, national, and international levels, eclipsing previous years' records. This progression highlights the faculty's commitment to fostering an environment conducive to innovation and creativity. The study underscores the faculty's pivotal role in sculpting individuals for global competencies, reflecting an emergent roadmap for academic institutions aspiring for international repute. However, it acknowledges its limitations in scope, advocating for future research to encompass broader educational contexts and integrate diverse measures of student success. These findings provide valuable insights for institutions striving to cultivate a culture of excellence and global readiness in the dynamic sphere of global education.